DETERMINATION OF THE FACTORS FOR POSITIONING “GREEN” ENERGY AS A CLIMATE NEUTRAL PRODUCT IN THE ENERGY MARKET - Борисяк, Олена (SWorldJournal, 2022)
The article is devoted to determining the factors of positioning “green” energy as a climate neutral product in the energy market based on the segmentation. Analysis of the factors involved in the formation of a segment of “green” energy in the energy mar